Physical Rehabilitation Services in Disasters and Emergencies: A Systematic Review - MOUSAVI, Ghasem (Iran J Public Health, 2019)
BACKGROUND: Physical rehabilitation, as one of the rehabilitation disciplines, can play a great role in humanitarian reliefs. The effectiveness of physical rehabilitation services is completely dependent on time of intervention, the importance of good timing in providing services during disasters is not well understood. The objective of this study was to systematically review the physical rehabilitation services provided in disasters and emergencies. METHODS: An electronic search of PubMed, Scopus, Cochrane, and PEDro (Physiotherapy Evidence Database) was undertaken from Jan 2000 to Sep 2017. All English studies reporting physical rehabilitation services in natural and man-made disasters were selected regardless of study design. The included studies were analyzed by descriptive and analytical method. RESULTS: Thirteen studies were included after reviewing by title, abstract and full text in this study. Most of the physical rehabilitation studies come back to recent years. Most of the disaster physical rehabilitation services were physiotherapy and occupational therapy. The physical rehabilitation experts have been attended in the affected area from the few first hours until several months after disasters in order to provide the required services to the affected population. CONCLUSION: There are few studies about physical rehabilitation services provided in the disaster-affected areas and this study showed that the services were limited and at different times. Physical rehabilitation services post disasters should have a comprehensive service model, like other health services. Therefore, it is necessary to conduct further studies to achieve this aim.